Educational software for photorealistic rendering in computer graphics (II) - Shi, Juan. (2012)
Rendering is one sub-topic in computer graphics. It is the process of generating image based on the 3D information of scene. Several rendering algorithm have been researched and applied to many fields in our life, like architecture, video games, simulators, movie or TV visual effects, and design visualization. Among them, Ray tracing algorithm is the one, which can produce high quality image as it naturally includes light paths such as specular reflection and transmission and is difficult to compute with those projective algorithms. As a result, ray tracing algorithm is becoming a more distinct subject with the increasing demand for realism.